2021
DOI: 10.3389/fcimb.2020.611113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) Tropical and Temperate Lineages: Uncovering Differences During Ehrlichia canis Infection

Abstract: The tick vector Rhipicephalus sanguineus is established as a complex of closely related species with high veterinary-medical significance, in which the presence of different genetic, morphological, and biological traits has resulted in the recognition of different lineages within taxa. One of the most striking differences in the “temperate” and “tropical” lineages of R. sanguineus (s.l.) is the vector competence to Ehrlichia canis, suggesting that these ticks tolerate and react differently to pathogen infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Narasimhan & Fikrig (2015) confirmed that symbionts might influence the vectorial competence of ticks because they modulate the immune status of the tick gut. Sanches et al (2021) compared infected and non-infected tissues of R. sanguineus from both lineages and observed that some proteins were only found under infected conditions. According to these authors, four of the most represented proteins present during E. canis infection could play important roles in the cement cone structure and function, which would favor infection in the tropical lineage of R. sanguineus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Narasimhan & Fikrig (2015) confirmed that symbionts might influence the vectorial competence of ticks because they modulate the immune status of the tick gut. Sanches et al (2021) compared infected and non-infected tissues of R. sanguineus from both lineages and observed that some proteins were only found under infected conditions. According to these authors, four of the most represented proteins present during E. canis infection could play important roles in the cement cone structure and function, which would favor infection in the tropical lineage of R. sanguineus.…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, four of the most represented proteins present during E. canis infection could play important roles in the cement cone structure and function, which would favor infection in the tropical lineage of R. sanguineus. On the other hand, proteins relating to detoxification and defensive response modulation were more represented in the temperate lineage of R. sanguineus and would have the capacity to reduce the vector competence of this lineage about E. canis (Sanches et al, 2021). It can therefore be asked whether this might be the reason why the temperate lineage of R. sanguineus is unable to transmit E. canis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few examples of the application of reversed-phase SPE through various proteomic studies have been collected in Table 1. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In these studies, different types of samples (e.g. various tissue specimens, cell lines, different biofluids, isolated exosomes, enriched samples for specific post-translational modifications [PTMs]) from humans, as well as other mammalian origins have been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…When the stationary phase is selected, one should always consider the origin and the amount of the samples to be purified. A few examples of the application of reversed‐phase SPE through various proteomic studies have been collected in Table 1 3–22 . In these studies, different types of samples (e.g.…”
Section: Introductionmentioning
confidence: 99%